Environmental impacts of restructuring the EU’s natural gas supply and consumption: Learnings from the 2022 energy crisis - Lucas F. Santos; Robert Istrate; Niall Mac Dowell; Gonzalo Guillén-Gosálbez (iScience)
Summary: In 2022, the European Union put forward the REPowerEU plan in response to Russia’s invasion of Ukraine, aiming at enhancing short-term energy security by diversifying imports and reducing natural gas demand while accelerating the deployment of renewable alternatives in the long term. Here, we quantify the life cycle environmental impacts of both REPowerEU’s short-term measures, including the controversial extended coal-fired power plant operations, and how the first year of the crisis was managed in practice. We find that the policy measures’ impact on greenhouse gas (GHG) emissions would be negligible, although they could have detrimental effects on other environmental categories. In practice, GHG emissions dropped by 8.6% driven by energy savings, yet other environmental burdens worsened, primarily due to coal and oil use. Our results could support the development and analysis of long-term policies to enhance energy security via natural gas demand reduction while considering multiple environmental sustainability indicators to avoid collateral damage.